Feminisme Radikal : Hubungan Antara Pakaian Dengan Tingginya Tingkat Pelecehan Seksual Pada Wanita - Sefia Esa Puspita A.; Vinda Olivia H.; Virna Muhdelifa D. (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Violence or sexual harassment is a problem that is quite serious and often occurs socially. In this case, it usually occurs in a problem that is complex. The rise of news on social media related to sexual violence experienced by some people is enough to shock the public. Most cases of sexual violence are experienced by a woman who is the victim. Cases of violence or sexual harassment against women are still an iceberg phenomenon. This is because many women who are victims of sexual harassment are reluctant to report what they have experienced. Violence or sexual harassment that occurs to women is often blamed on the way they dress. In fact, if you look at clothes, it is not one of the main causes of women becoming victims of sexual harassment. Violence or sexual harassment that occurs never looks at any clothes, in fact often the victim of sexual harassment is a woman who wears closed clothes. In addition, violence or sexual harassment can also be caused by a patriarchal culture that dominates and seems to justify the action. Where in patriarchal culture itself men are often considered more dominant and have a higher position than women. Therefore, men feel they have more power over women and can act as they please. Until now, patriarchal culture is still developing in society. Even though this shouldn't have been done. Therefore, there is a need for radical feminism with the aim of making changes in society and obtaining equality between men and women, especially in obtaining equal rights in society from a social and economic point of view.